2017
DOI: 10.1200/po.17.00014
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal-Jejunal Flexure GI Stromal Tumor Frequently Heralds Somatic NF1 and Notch Pathway Mutations

Abstract: Purpose GI stromal tumors (GISTs) are commonly associated with somatic mutations in KIT and PDGFRA. However, a subset arises from mutations in NF1, most commonly associated with neurofibromatosis type 1. We define the anatomic distribution of NF1 alterations in GIST. Methods We describe the demographic/clinicopathologic features of 177 patients from two institutions whose GISTs underwent next-generation sequencing of ≥315 cancer-related genes. Results We initially identified six (9.7%) of 62 GISTs with NF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Importantly, no individuals described in this and previous studies had visible plexiform neurofibromas (0/127 ≥9 years) or histopathologically confirmed cutaneous (0/59 ≥19 years) or subcutaneous neurofibromas (0/37 ≥19 years) (Table S6). 4,25,26 Similar to the NF1 p.Arg1809 cohort, no symptomatic OPGs were observed in the studied group. In the current study, none of the individuals showed symptomatic spinal neurofibromas (Table 1), although in the original report a single symptomatic spinal tumor was found; 4 nevertheless, even combined that remains significantly less prevalent than in the cohort of individuals with the NF1 missense pathogenic variants at residues 844–848 ( P < 0.0001, statistically significant after B–H correction at FDR 0.01).…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Importantly, no individuals described in this and previous studies had visible plexiform neurofibromas (0/127 ≥9 years) or histopathologically confirmed cutaneous (0/59 ≥19 years) or subcutaneous neurofibromas (0/37 ≥19 years) (Table S6). 4,25,26 Similar to the NF1 p.Arg1809 cohort, no symptomatic OPGs were observed in the studied group. In the current study, none of the individuals showed symptomatic spinal neurofibromas (Table 1), although in the original report a single symptomatic spinal tumor was found; 4 nevertheless, even combined that remains significantly less prevalent than in the cohort of individuals with the NF1 missense pathogenic variants at residues 844–848 ( P < 0.0001, statistically significant after B–H correction at FDR 0.01).…”
Section: Resultsmentioning
confidence: 53%
“…4 None of the individuals had externally visible plexiform neurofibromas or histopathologically confirmed cutaneous or subcutaneous neurofibromas (all P < 0.0001, statistically significant at FDR of 0.01 after B–H correction when compared with the cohort of individuals with the NF1 missense pathogenic variants affecting codons 844–848 and the “classic” NF1-affected population, Table 2). Combining data from this and previous studies 4,25,26 for plexiform (0/127 ≥9 years), cutaneous, and subcutaneous neurofibromas (0/59 and 0/37 ≥19 years, respectively), we estimate in post hoc power calculation that these sample sizes would allow to detect the presence of plexiform, cutaneous, and subcutaneous neurofibromas with a prevalence of at least 3%, 7%, and 10%, respectively with a power of 95%. However, we cannot speculate about the risk for internal neurofibromas in this cohort as MRI screening was not routinely done in most of the asymptomatic individuals.…”
Section: Discussionmentioning
confidence: 98%
“…Sequencing was performed on formalin-fixed paraffin-embedded (FFPE) sections (6 tumors from National Cancer Institute (NCI), 1 tumor from Oregon Health & Science University (OHSU) and 1 tumor from University of California, San Diego (UCSD). FoundationOne-Heme Next Generation Sequencing (NGS) was performed on Tumor 1 as previously described [16]. Briefly, DNA was extracted from FFPE sections with a minimum of 20% tumor tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Other GIST mutation types also associate with predictable clinicopathologic features. For example, KIT exon 9-mutant GISTs nearly always develop in the small intestine (9); neurofibromin 1-mutant (NF1-mutant) GISTs are more commonly found in the duodenojejunal flexure (10); and succinate dehydrogenase-deficient (SDH-deficient) GISTs are indolent, multifocal, and among the few GISTs -along with those driven by kinase fusions -that metastasize via the lymphatic system (11,12). The underlying biologic mechanisms linking mutation type and clinicopathologic features are not well understood.…”
Section: Introductionmentioning
confidence: 99%